High-Resolution Structural Analysis of Chromatin at Specific Loci: Saccharomyces cerevisiae Silent Mating-Type Locus HMRa - Ravindra, Anish (American Society for Microbiology, 1999)
Genetic and biochemical evidence implicates chromatin structure in the silencing of the two quiescent mating-type loci near the telomeres of chromosome III in yeast. With high-resolution micrococcal nuclease mapping, we show that the HMRa locus has 12 precisely positioned nucleosomes spanning the distance between the E and I silencer elements. The nucleosomes are arranged in pairs with very short linkers; the pairs are separated from one another by longer linkers of ∼20 bp. Both the basic amino-terminal region of histone H4 and the silent information regulator protein Sir3p are necessary for the organized repressive chromatin structure of the silent locus. Compared to HMRa, only small differences in the availability of the TATA box are present for the promoter in the cassette at the active MATa locus. Features of the chromatin structure of this silent locus compared to the previously studied HMLα locus suggest differences in the mechanisms of silencing and may relate to donor selection during mating-type interconversion.